The Liability of Ordinary Soldiers for Crimes of Aggression - David Rodin (Washington University Global Studies Law Review, 2007)
This “liability gap”-the fact that sovereigns and statesmen, but not subordinate officers and soldiers, are liable for jus ad bellum offences-is one of the great puzzles of international law and ethics. In this essay I examine the philosophical foundation of combatants’ war rights and the basis for liability for ad bellum offences. I conclude that there is at least a theoretical basis for extending liability for the crime of aggression to ordinary soldiers and lower ranking officers.
Keywords: Aggression (International law); Government liability; Military personnel; Self defense (International law); International; Self defence (International law)